Curriculum Innovation for the Excellent Madrasah Aliyah Program Based on Pesantren - Royani, Ahmad; Mustajab; Mursalim; Muhith, Abd.; a Ghani, Muhammad Faizal (Cendekia: Kependidikan dan Kemasyarakatan, 2024)
This research examines curriculum innovations in Islamic boarding school-based madrasas. Holistic learning, which integrates religious education (Islamic boarding school, also called pesantren) and formal education, is a powerful instrument for school admission to attract more students. Thus, Islamic boarding school-based madrasah curriculum needs to develop innovation to meet the needs of society consistently and adapt to the evolving educational landscape. This research aims to review the curriculum innovations carried out by pesantren-based Madrasah Aliyah to ensure relevance and effectiveness. This research employed a qualitative research design with a case study approach. It established a complex picture of excellent-based madrasa curriculum innovation by examining expressions, detailed reports, and conducting studies in natural situations with various stakeholders. This research concludes that pesantren curriculum innovation is implemented through some stages, including 1) doing needs analysis, 2) formulating and answering philosophical questions, 3) determining the curriculum design, and 4) creating a master plan: development, implementation, and assessment or evaluation for sustainable improvement.